2023
DOI: 10.1073/pnas.2212613120
|View full text |Cite
|
Sign up to set email alerts
|

The PRAK-NRF2 axis promotes the differentiation of Th17 cells by mediating the redox homeostasis and glycolysis

Abstract: Oxidative stress is a key feature in both chronic inflammation and cancer. P38 regulated/activated protein kinase (PRAK) deficiency can cause functional disorders in neutrophils and macrophages under high oxidative stress, but the precise mechanisms by which PRAK regulates reactive oxygen species (ROS) elimination and its potential impact on CD4+ T helper subset function are unclear. The present study reveals that the PRAK-NF-E2-related factor 2(NRF2) axis is essential for maintaining the intracellular redox h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…S10 I ). Because Th17 cells are characterized by distinctive homeostasis involving the upregulation of glycolysis ( 27 29 ), we focused on the metabolic genes associated with respiratory functions. Numerous glycolysis-related gene expressions exhibited downregulation in Il6 KO rats, whereas the majority of TCA cycle gene expressions remain unaffected ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S10 I ). Because Th17 cells are characterized by distinctive homeostasis involving the upregulation of glycolysis ( 27 29 ), we focused on the metabolic genes associated with respiratory functions. Numerous glycolysis-related gene expressions exhibited downregulation in Il6 KO rats, whereas the majority of TCA cycle gene expressions remain unaffected ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, IL-21 + cells around pulmonary vessels, which resulted in remodeling in the SuHx model in WT rats, were rarely seen in Il6 KO rats. mRNA levels of genes involved in glycolysis, which is enhanced during differentiation of Th17 cells ( 27 29 ), were up-regulated in an IL-6-dependent manner in CD4 + cells of the SuHx lungs. Taken together, these results suggest that activation of AHR triggers a positive feedback loop of Th17 cell differentiation via the IL-6/AHR signaling axis in PAH.…”
Section: Discussionmentioning
confidence: 99%
“…22 The Nrf2 promoted the differentiation of T helper 17 cells. 23 T helper 17 cells promoted inflammatory responses through interleukin-17. 24 The association between p-Nrf2 and the tumor microenvironment and the relationship between tumor-infiltrating T cells and peripheral blood lymphocytes has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ROS indirectly induces an antitumor effect by boosting immune cells. For example, PRAK deficiency-induced ROS accumulation impairs the differentiation of Th17 cells and antitumor immunity though disrupting phosphorylation of STAT3 [ 57 ]. ROS spurs dendritic cell maturation by activating p38-MAPK and ERK1/2 [ 58 ].…”
Section: Oxidative Stress and Tumor Immunitymentioning
confidence: 99%
“…For example, tumor-associated neutrophils produce O 2 • mediated by NOX2, inhibiting the expansion of γδ T cells, which promote tumor development by producing IL-17 [ 81 ]. Recent studies have indicated that the PRAK-NRF2 axis, which is associated with ROS, is essential for Th17 cells to maintain antitumor effects [ 57 ]. Phosphatase PAC1, as an oxidative stress responder [ 82 ] and a negative regulator of the immune system, specifically inhibits T lymphocyte defense and promotes tumor immune escape [ 83 ].…”
Section: Oxidative Stress and Tumor Immunitymentioning
confidence: 99%